Applying World Dental Federation Theoretical Framework for Oral Health in a General Population - Hanna Ahonen; Amir Pakpour; Ola Norderyd; Anders Broström; Eleonor I. Fransson; Ulrika Lindmark (Elsevier, 2022)
Introduction: The World Dental Federation (FDI) has recently proposed a new definition and theoretical framework of oral health. The theoretical framework includes 4 main components and describes the relationships amongst them. In 2020, an international work group proposed the minimum Adult Oral Health Standard Set (AOHSS) of variables to measure oral health, which was mapped onto the FDI's theoretical framework. By using an empirical data set, the proposed variables in the AOHSS and the potential interactions amongst the components of the FDI's theoretical framework can be tested. The purpose of this research was to investigate structural relations of the components of the FDI's theoretical framework of oral health based on data from a general adult population. Methods: Data from a previously conducted Swedish cross-sectional study focusing on oral health were utilised (N = 630; women, 55.2%; mean age, 49.7 years [SD, 19.2]). Variable selection was guided by the AOHSS. Structural equation modeling was used to analyse relationships amongst the components of the FDI's theoretical model (core elements of oral health, driving determinants, moderating factors, and overall health and well-being). Results: The Oral Health Impact Profile (OHIP)-14, xerostomia, and aesthetic satisfaction had statistically significant direct effects on overall health and well-being (p < .05). Driving determinants and moderating factors had statistically significant direct effects on all core elements of oral health (p < .05) except aesthetic satisfaction (p = .616). The predictors explained 24.1% of the variance of the latent variable overall health and well-being. Based on several indices, the proposed model showed acceptable model fit. Conclusions: The FDI's theoretical framework can be used to describe different components of oral health and the relationship amongst them in an adult general population. Further research based on the FDI's theoretical framework in other populations and settings is needed to explore complex interactions and possible relationships that form oral health and to investigate other or additional important social determinants.